EFFECT OF PRE- AND POSTHARVEST APPLICATION OF 1-METHYLCYCLOPROPENE ON THE MATURATION OF YELLOW PITAHAYA (Selenicerus megalanthus Haw) - SERNA C., Liliana; TORRES V., Laura S.; AYALA A., Alfredo A. (Vitae, 2012)
The effect of pre- and postharvest applications of 200 and 400 μgL-1 aqueous solutions of 1-methylcyclopropene (1-MCP) on yellow pitahaya (maturity stage 3) was assessed. Changes in respiratory rate, color, firmness, soluble solids content, titratable acidity, maturity index, weight loss and commercial preservation were measured. Results showed that the preharvest application of 400 μgL-1 1-MCP enhanced fruit color, preserved firmness, and reduced weight loss and maturity index of fruits. It is suggested that these results were explained by the reduction of available membrane receptors able to bind ethylene, thus increasing ethylene sensitivity and response magnitude. The preharvest application of 1-MCP could potentially be used to accelerate pitahaya fruit ripening. The preharvest application of 200 μgL-1 1-MCP resulted in smaller changes in color and titratable acidity vs. control. Total soluble solids and pH were not significantly affected by the treatments. The postharvest application of 1-MCP maintained the texture of fruits by three additional days when compared to the untreated control.